Promoting and sustaining a quality teacher workforce - LeTendre, Gerald K.; Wiseman, Alexander W. 1968- (International perspectives on education and society, 2015)
Teacher effectiveness and teacher quality have become the focus of intense international attention and concern. Around the world, governments are modifying existing certification requirements or implementing value-added modeling in order to qualify teachers without planning for the long-term consequences of these actions. The book brings together scholars from multi-disciplinary and international backgrounds to address two critical areas: (1) what existing cross-national measures of teacher effectiveness and teacher quality are most promising, and how can these be aligned to maximize their research potential; and (2) what core constructs of teacher quality or effectiveness are missing, and how can cross-national research help identify these. Identifying both what is used and what is missing in the international and comparative analysis and reform of teacher quality is key to informing evidence-based educational policy formation around teacher quality.